Tác động của mạng xã hội đến mức sẵn lòng trả áp dụng công nghệ sản xuất nông nghiệp: Trường hợp san phẳng mặt ruộng lúa dùng tia laser tại đồng bằng Sông Cửu Long - Phùng Ngọc, Triều; Lê Thanh, Loan; Trần Đức, Luân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The article analysed the impact of social information sources on the adoption of laser land leveling (LLL) technology in the Mekong Delta. This study uses the BDM auction method to elicit the willingness to pay for LLL technology adoption among 167 decision-making farmers in rice cultivation households in An Giang and Kien Giang provinces. The research findings indicate that the scale of farmers’ social network connections, media channels, information from NGO (Non-governmental Organization) projects, peer discussions about LLL, the unevenness of the field surface, and the coefficient reflecting the farmers’ assets positively impact their willingness to pay, with a significance level of 5%. These findings provide a basis for policies to promote the adoption and dissemination of agricultural sustainable technologies and new techniques specifically in rice cultivation and generally in agricultural production.